Surface roughness and surface hardness of acrylic resins exposed to cuttle bone powder polishing agents - Hummudi , Israa M; Yaseen, Ihab N; Mageed, Melad S; Alatrakchi , Ghasak GF (Journal of Baghdad College of Dentistry, 2025)
Background: Preserving oral health for denture wearers is of high priority. It can be significantly affected by the degree of surface roughness of the dentures. So, it is essential to refine the dentures properly before delivering to the patient. The abrasive materials should offer a smoother surface without affecting the properties of denture bases. This study aimed to evaluate the impact of various abrasive agents on both surface roughness and surface hardness of acrylic resin denture base material. The abrasive agents selected for this study were pumice and cuttlebone Materials and Methods: A total of 60 heat-polymerized polymethylmethacrylate specimens (65x10 x2.5 mm) were constructed and grouped into control (n=10) finished with pumice size (120 µm) and experimental (n=20) finished with cuttlebone powder sizes (150 µm) and (120 µm). Then they were divided into two groups: 30 specimens were subjected to profilometer surface roughness analysis and 30 specimens were subjected to Shore D hardness tester. Polished of acrylic resin surfaces specimens were assessed by scanning electron microscopy and Atomic Force microscopy. Results: The acrylic resin specimens finished with cuttlebone powder (experimental)size 150 µm and 120 µm showed the least surface roughness in comparison with specimens finished with pumice (control). ANOVA and LSD tests showed significant differences (p˂0.001) between the control and experimental groups. In surface hardness test, ANOVA - test revealed non- significant differences at the (p ˃ 0.05) level between control and experimental groups. Conclusion: This study demonstrated that cuttlebone powder has successfully reduced the surface roughness of denture base material. Moreover, surface hardness was not affected by the cuttlebone polishing agent which suggests the successful applicability of the tested particle size for dental practitioners.